The relationship between young children’s personal values and their teacher-rated behaviors in the classroom - Scholz-Kuhn, Ricarda; Makarova, Elena; Bardi, Anat; Döring, Anna K. (Frontiers in Education, 2023)
There has been little research on the relationships between children's personal values and the behaviors that express such values in the school context. In the present study, we examined for the first time with children at this young age, the relations between values and their value-related behaviors, i.e., supportive, disciplined, learning-oriented and achievement-oriented, in the primary school context. The sample consisted of 952 primary school children (51.5 % boys; Mage = 7.93; SD = .35). Data used in this study were collected in 2022 in Switzerland. A multilevel analysis confirmed the hypothesis that systematic relationships between values and teacher-rated behaviors can be demonstrated with young children. However, gender was the strongest predictor of teacher-rated children’s classroom behaviors. The results highlight the significance of understanding children’s value-behavior relations, teachers’ possible gender stereotypes of children’s behaviors and its practical importance in the school context.